The effect of non-contributory pensions on labour supply and private income transfers: Evidence from Singapore - Yanying Chen; Yi Jin Tan (IZA Journal of Labor Policy, 2018)
Non-contributory pensions are becoming increasingly prevalent worldwide. As their effects are likely to be context-dependent, evaluating their effects in a wide range of settings is important for establishing the external validity of the non-contributory pension literature. We use a new monthly panel dataset and a difference-in-differences strategy to study the effect of a new non-contributory pension in Singapore (the Silver Support Scheme or SSS) on labour supply, work expectations, private cash transfers, and expenditure, 1 year after its implementation. We find no evidence that receiving SSS payouts led to a fall in labour supply, work expectations, or the receipt of private cash transfers in the first year after SSS implementation-our estimated effects for these outcomes are statistically insignificant and are either negative but close to zero or positive. Our point estimates of the effects of receiving SSS payouts on expenditure are positive but too imprecise to allow us to make any definitive conclusions. Lastly, we do not find evidence of anticipatory effects among younger individuals who are not age-eligible for payouts yet. These results, when coupled with our finding in a companion paper that the SSS improved recipients' subjective well-being, suggest that the SSS was successful in improving recipients' welfare without substantial crowding out of private transfers or changes in labour market behaviour of current and future SSS beneficiaries.
Keywords: H3; H4; I3; J2; 330; Non-contributory pensions; Labour supply; Private income transfers; Crowding out